2018
DOI: 10.1002/jbmr.3559
|View full text |Cite
|
Sign up to set email alerts
|

Structural Adaptations in the Rat Tibia Bone Induced by Pregnancy and Lactation Confer Protective Effects Against Future Estrogen Deficiency

Abstract: The female skeleton undergoes substantial structural changes during the course of reproduction. Although bone mineral density recovers postweaning, reproduction may induce permanent alterations in maternal bone microarchitecture. However, epidemiological studies suggest that a history of pregnancy and/or lactation does not increase the risk of postmenopausal osteoporosis or fracture and may even have a protective effect. Our study aimed to explain this paradox by using a rat model, combined with in vivo micro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…Some studies suggested that the history of breastfeeding can significantly increased the risk of PMOP [13], while some studies showed that prolonged breastfeeding duration was an independent risk factor for the development of PMOP rather than breastfeeding itself [14, 15]. Conversely, some studies suggested that the history of breastfeeding may increase the bone mass density, which significantly decreased the incidence of PMOP [16], whereas other studies demonstrated a non-significant relationship between breast-feeding and PMOP [9, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested that the history of breastfeeding can significantly increased the risk of PMOP [13], while some studies showed that prolonged breastfeeding duration was an independent risk factor for the development of PMOP rather than breastfeeding itself [14, 15]. Conversely, some studies suggested that the history of breastfeeding may increase the bone mass density, which significantly decreased the incidence of PMOP [16], whereas other studies demonstrated a non-significant relationship between breast-feeding and PMOP [9, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple more recent studies have confirmed the relationship of bone remodeling to calcium variation in lactating female rats, highlighting that it may serve a key role in restoring bone health associated with calcium loss (Bowman et al, 2002;Miller and Bowman, 2007;Ross and Sumner, 2017). This is further supported by ongoing research indicating that female bone microarchitecture (both trabecular and cortical) adapts in a protective way to the negative effects of reproduction and estrogen loss (de Bakker et al, 2018a;de Bakker et al, 2018b).…”
mentioning
confidence: 78%
“…The effects of sexual dimorphism and species-specific bone histology could also affect our results. Given the large effect of rat lactation and reproduction on bone micro-architecture in the female sex (de Bakker et al, 2018b), future research investigating giant rat bone histology in fossils should aim to account for sexual dimorphism. However, our results constitute the first micro-anatomical record of remodeled cortical bone in a fossil giant rat in SEA.…”
Section: Discussionmentioning
confidence: 99%
“…For many populations in industrialized or sedentary contexts, parity and lactation would be expected to have even less of an effect (Henderson III et al, 2000). Furthermore, animal models suggest that repeated reproductive events alter bone microstructure in ways that may prove beneficial after menopause (de Bakker et al, 2017, 2018), but thus far we are unaware of similar findings in humans.…”
Section: Discussionmentioning
confidence: 99%